Book Review - Beth DiNatale Johnson (Names)
Tempest: Hurricane Naming and American Culture. By Liz Skilton. Baton Rouge: Louisiana State University Press. 2023. Pp. 320 (Paperback). $40.00. ISBN 13: 978-0-8071-7996-3.